2021
DOI: 10.1007/s00418-020-01953-y
|View full text |Cite
|
Sign up to set email alerts
|

Expression and enhancement of FABP4 in septoclasts of the growth plate in FABP5-deficient mouse tibiae

Abstract: In our previous study, fatty acid-binding protein 5 (FABP5) was expressed in septoclasts with long processes which are considered to resorb uncalcified matrix of the growth plate (GP) cartilage, and no apparent abnormalities were detected in the histo-architecture of the GP of FABP5-deficient (FABP5−/−) mice. Those finding lead us to hypothesize that another FABP can compensate the deletion of FABP5 in septoclasts of its gene-mutant mice. Based on the hypothesis, the present study examined the expression level… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 56 publications
0
4
0
Order By: Relevance
“…Sections were subsequently treated with 4,6‐diamidino‐2‐phenylindole dihydrochloride (DAPI, ImmunoBioScience, Mukilteo, WA, USA) for nuclear staining. The specificity of the anti‐rat E‐FABP antibody used in this study has been described previously (Bando et al, 2021; Kitanaka et al, 2003; Owada et al, 2001; Sakashita et al, 2022). According to the findings of our previous study (Bando et al, 2018), the goat anti‐PDGFRβ antibody can be used as a septoclast marker instead of the rabbit anti‐E‐FABP antibody to avoid the cross‐reaction by primary antibodies from the same host species for double immunostaining with rabbit anti‐collagen antibodies.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Sections were subsequently treated with 4,6‐diamidino‐2‐phenylindole dihydrochloride (DAPI, ImmunoBioScience, Mukilteo, WA, USA) for nuclear staining. The specificity of the anti‐rat E‐FABP antibody used in this study has been described previously (Bando et al, 2021; Kitanaka et al, 2003; Owada et al, 2001; Sakashita et al, 2022). According to the findings of our previous study (Bando et al, 2018), the goat anti‐PDGFRβ antibody can be used as a septoclast marker instead of the rabbit anti‐E‐FABP antibody to avoid the cross‐reaction by primary antibodies from the same host species for double immunostaining with rabbit anti‐collagen antibodies.…”
Section: Methodsmentioning
confidence: 99%
“…Electron microscopic observation was performed using the methods described in our previous study (Bando et al, 2021). After perfusion with 4% paraformaldehyde in 0.1 M phosphate buffer, the tibiae were dissected and immersed in the same fixative overnight at 4°C, and for preparation of specimens for electron microscopy, the tibiae were immersed in 2% glutaraldehyde in 0.1 M cacodylate buffer (pH 7.4) for 2 h at 4°C and postfixed with 1% OsO4 for 2 h at 4°C.…”
Section: Methodsmentioning
confidence: 99%
“…In their previous work, Bando et al (2017) were unable to detect overt histological abnormalities in the growth plate of FABP5-deficient mice. Since it has been reported that FABP5 deficiency could be functionally compensated by another FABP subtype (Owada et al 2002), Bando et al (2021) have now investigated by immunohistochemistry the presence of FABP3, -4, -5, and -7 in septoclasts in mouse tibiae. They were able to detect FABP4 in septoclasts of FABP5-deficient mice and found that the number of FABP4-positive septoclasts was increased about 2.5fold as compared to wild-type mice (Fig.…”
Section: A Tango For One: Fabp4 As a Substitute For Fabp5 In Cartilage Septoclastsmentioning
confidence: 99%
“…Note the increased number of FABP4-immunoreactive cells in FABP5 −/− mice (g). From Bando et al (2021) FABP5 and FABP4 are important for the shape and function of septoclasts.…”
Section: A Tango For One: Fabp4 As a Substitute For Fabp5 In Cartilage Septoclastsmentioning
confidence: 99%